A Hazard Analysis and Critical Control Point (HACCP) plan and a food safety tool kit for common beans in Uganda - International Center for Tropical Agriculture; National Agricultural Research Organization, Uganda; Kenya Agricultural and Livestock Research Organization (International Center for Tropical Agriculture, 2018)
The purpose of this toolkit is to equip stakeholders across the food value chain with a cost-effective system for control of food quality and safety right from farm to reception of raw materials and through production, storage, distribution, sale and service to the final consumers. The expected outcome is a reduction in the loss of the quantity of beans due to mismanagement along the value chain. This toolkit can be used by the value chain actors across the bean value chain who include: farmers, processors, and food vendors to ensure that food products are safe for human consumption. This toolkit is a communication toolkit for all the food chain value actors across the bean value chain. It should enable readers to improve common bean food safety and quality control for consumption purposes. (2018-03-19)